Concurrent curing kinetics of an anhydride-cured epoxy resin and polydicyclopentadiene. (9th July 2015) - Rohde, Brian J.; Robertson, Megan L.; Krishnamoorti, Ramanan
Abstract: The development of interpenetrating polymer networks provides a route to create tough materials that maintain high strength and stiffness, suitable for meeting the demands of an off-shore wind turbine environment. This work has focused on a system composed of diglycidyl ether of bisphenol A (DGEBA)-based epoxy resin, contributing high tensile strength and modulus, and polydicyclopentadiene (polyDCPD), which has a higher toughness and impact strength as compared to other thermoset polymers. In situ Fourier transform infrared spectroscopy was used to explore the reaction kinetics in neat, diluted and sequentially cured mixtures of epoxy resin and polyDCPD. There were significant differences in the rate of network formation in the two neat systems, as the rate of anhydride curing of the epoxy was extremely slow at the temperatures required for reasonably measurable dicyclopentadiene (DCPD) ring-opening metathesis polymerization. The dissimilar kinetics of these two systems were leveraged in the design of a sequential curing protocol in which the DCPD was first cured in the presence of the epoxy resin components, followed by curing of the epoxy resin at an elevated temperature. The curing kinetics of the macroscopically phase separated domains of the epoxy resin components in the presence of the polyDCPD network behaved as expected for a diluted epoxy resin. These results provide the kinetic basis for future studies to prepare interpenetrating polymer networks which employ thermodynamic control of phase separation such as through the addition of compatibilizing molecules. Graphical abstract: